2021
DOI: 10.1101/2021.08.10.455254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HDAC9structural variants disruptingTWIST1transcriptional regulation lead to craniofacial and limb malformations

Abstract: Structural variants (SVs) can affect protein-coding sequences as well as gene regulatory elements. However, SVs disrupting protein-coding sequences that also function as cis-regulatory elements remain largely uncharacterized. Here, we show that craniosynostosis patients with SVs containing the Histone deacetylase 9 (HDAC9) protein-coding sequence are associated with disruption of TWIST1 regulatory elements that reside within HDAC9 sequence. Based on SVs within the HDAC9-TWIST1 locus, we defined the 3' HDAC9 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Long et al ( 97 ) combined epigenomic maps, enhancer reporter assays, and endogenous deletion of enhancers in both in vitro–derived CNCCs and mice to show that structural variants causing Pierre Robin sequence disrupt enhancers more than 1 Mb away from SOX9 . Hirsch et al ( 59 ) used similar approaches to demonstrate that structural variants encompassing parts of HDAC9 , a neighboring gene to the craniofacial transcription factor TWIST1 , cause craniosynostosis through disruption of TWIST1 enhancers. These studies were in part successful at fine mapping the regulatory elements underlying disease-causing mutations because of their relatively large effect size, but this becomes more challenging for variants associated with common variation in facial shape or risk for nsCL/P or craniosynostosis.…”
Section: Functional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Long et al ( 97 ) combined epigenomic maps, enhancer reporter assays, and endogenous deletion of enhancers in both in vitro–derived CNCCs and mice to show that structural variants causing Pierre Robin sequence disrupt enhancers more than 1 Mb away from SOX9 . Hirsch et al ( 59 ) used similar approaches to demonstrate that structural variants encompassing parts of HDAC9 , a neighboring gene to the craniofacial transcription factor TWIST1 , cause craniosynostosis through disruption of TWIST1 enhancers. These studies were in part successful at fine mapping the regulatory elements underlying disease-causing mutations because of their relatively large effect size, but this becomes more challenging for variants associated with common variation in facial shape or risk for nsCL/P or craniosynostosis.…”
Section: Functional Studiesmentioning
confidence: 99%
“…While both Long et al ( 97 ) and Hirsch et al ( 59 ) provided strong evidence for causality by re-creating variants through genome editing in their endogenous regulatory context, such an approach is both time and resource intensive, especially if performed in relevant model systems, such as human pluripotent stem cell–derived CNCCs and their derivatives, or mice. A set of attractive in-between options is provided by massively parallel reporter assays and their numerous variants, all of which involve transfection or transduction of a library of DNA constructs consisting of regulatory elements of interest upstream of a reporter gene with genetic barcodes, allowing for sequencing-based readouts of all regulatory element activity simultaneously [reviewed by Inoue & Ahituv ( 69 )].…”
Section: Functional Studiesmentioning
confidence: 99%
“…A relevant recent work by Hirsch et al from Birnbaum’s lab showed that structural variants (SVs) disrupting protein-coding sequences can also function as cis-regulatory elements [ 70 ]. They showed that craniosynostosis patients with SVs containing the Histone deacetylase 9 ( HDAC9 ) protein-coding sequence are associated with disruption of TWIST1 regulatory elements that reside within the HDAC9 sequence.…”
Section: Current Practice: Genomic Annotation and Establishing Causalitymentioning
confidence: 99%
“…The zebrafish enhancer assay showed that some candidate enhancers drove specific GFP expression in branchial arches and other facial bones. By this, Hirsch et al provided an insight into the spatiotemporal regulatory network that controls Twist1 expression in the developing craniofacial tissues [ 70 ]. These studies exemplify the promise of functional studies in animal models for deciphering non-coding regulatory regions (by deleting or disrupting them) and understanding disease causality, which remains a major challenge as of now.…”
Section: Current Practice: Genomic Annotation and Establishing Causalitymentioning
confidence: 99%